Improved detection of tides at Europa with radiometric and optical tracking during flybys. (July 2015) - Park, Ryan S.; Bills, Bruce; Buffington, Brent B.; Folkner, William M.; Konopliv, Alexander S.; Martin-Mur, Tomas J.; Mastrodemos, Nickolaos; McElrath, Timothy P.; Riedel, Joseph E.; Watkins, Michael M.
Abstract: Due to its eccentric orbit about Jupiter, Europa experiences periodic tidal deformation, which causes changes in its gravitational field and induces both radial and transverse displacements of the surface. The amplitude and phase of these tidal changes are diagnostic of internal structure, and can be measured with sufficient radiometric and optical tracking of a spacecraft during a series of flyby encounters with Europa. This paper presents results of the simulated accuracy for recovery of the tides of Europa through measuring the second-degree tidal Love numbers k 2, h 2, and l 2 . A reference trajectory, which consists of a total of 45 close flybys, was considered and a detailed covariance analysis was performed. The study was based on Earth-based Doppler tracking during ± 2 h of each periapsis passage and surface imaging data taken below 500 km altitude. The result shows that the formal uncertainty of the second-degree tidal Love numbers can be estimated to be σ k 2 = 0.01, σ h 2 = 0.02, and σ l 2 = 0.01, which is sufficient to constrain the global ice thickness to about 10 km under reasonable assumptions. Moreover, the forced librations of Europa can be measured to 0.3″ accuracy, which can further constrain Europa's interior structure. Highlights: We present the feasibility of measuring Europa's tides from multiple flybys. Europa's tidal deformation can be measured from radio data and onboard imagery. Europa's global ice thickness can be constrained to about 10 km. The forced libration of Europa can be measured to extremely high precision.